Analysis of the effect of ultrasonic agitation on the cleaning of root canals using different periods during the final irrigation - Felipe Xavier; Giselle Nevares; Diana Santana de Albuquerque; Luciana Ferraz Gominho; Rafaela Leal de Alcântara Dellazari; Rodrigo Sanches Cunha; Joedy Maria Costa Santa Rosa (Revista Sul-Brasileira de Odontologia, 2015)
The ultrasonic agitation was introduced as an adjuvant to conventional chemo-mechanical debridement during endodontic treatment to overcome the persistence of biofilms. Objective: To verify the cleaning of root canals irrigated with sodium hypochlorite (NaOCl) and ethylenediaminetetraacetic acid (EDTA), with or without an ultrasonic agitation, using different time periods and images obtained by scanning electron microscope (SEM). Material and methods: Forty mandibular incisors were cleaned, shaped and randomly divided into five groups according to the final irrigation protocol: SH10 group (ultrasonic agitation with NaOCl for 10 s), SH30 group (ultrasonic agitation with NaOCl for 30 s), SHE30 group (ultrasonic agitation with NaOCl and EDTA for 10 s), SHE90 group (ultrasonic agitation with NaOCl and EDTA for 30 s), and control group (NaOCl and EDTA without ultrasonic agitation). The teeth were prepared and analyzed by SEM at ×2000. The Kruskal–Wallis test was used with a 5% level of significance. Results: For the cervical and medial thirds, there was no statistically significant difference in cleaning among the protocols used (p > 0.05). For the cleaning of the apical third, SHE90 group demonstrated a significant difference (p < 0.05), as compared to the control and SH10 groups. Conclusion: For the final irrigation, an ultrasonic agitation with NaOCl and EDTA for 30 s allowed a better cleaning of the debris in the apical third of the root canal.